Coexistence of ferroelectric vortex domains and charged domain walls in epitaxial BiFeO3 film on (110)O GdScO3 substrate - Qi, Yajun (2013)
The occurrence of ferroelectric charged domain walls (CDWs) which was thought to be energetically unstable is observed, together with a ferroelectric vortex structure composed of 109° and 180° domains near an epitaxial BiFeO3/GdScO3 interface. The CDW and vortex affect the domain arrangement, domain configuration, and hence tune the domain size distribution.